Pragmatic cluster randomised double-blind pilot and feasibility trial of an active behavioural physiotherapy intervention for acute non-specific neck pain: A mixed-methods protocol - Taweewat Wiangkham (2020)
© 2019 Author(s). Introduction Non-specific neck pain causes pain and disability and contributes substantial socioeconomic burden internationally. Up to 50% of adults experience neck pain annually, leading to reduced the quality of life. An active behavioural physiotherapy intervention (ABPI) may be feasible to manage patients with acute non-specific neck pain to prevent transition to chronicity. A recent pilot and feasibility trial investigating an acute whiplash-associated disorder population found potential value of the ABPI with 95% of participants fully recovered (Neck Disability Index: NDI ≤4, compared with 17% in the standard physiotherapy arm); supporting a definitive trial. Qualitative findings from the physiotherapists supported the potential of the ABPI in a non-specific neck pain population. Methods and analysis Two phases: (1) Pragmatic cluster randomised double-blind, parallel 2-arm (ABPI vs standard physiotherapy intervention) pilot and feasibility trial to evaluate the procedures and feasibility of the ABPI for the management of acute non-specific neck pain. Six physiotherapy departments from six public hospitals in Thailand will be recruited and cluster randomised by a computer-generated randomisation sequence with block sampling. Sixty participants (30 each arm, 10 per hospital) will be assessed at baseline and 3 months following baseline for NDI, Numerical Rating Scale for pain intensity, cervical range of motion, fear-avoidance beliefs questionnaire and EuroQol-5 dimensions 5 levels outcomes, and (2) Embedded qualitative study using semistructured interviews to explore acceptability of the ABPI to participants (n=12) and physiotherapists (n=3). Descriptive analysis of the quantitative data and interpretative phenomenological analysis to code and analyse qualitative data (deductive and inductive) will inform feasibility for a future definitive trial. Ethics and dissemination This trial is approved by the Naresuan University Institutional Review Board (NUIRB-0380/61).